2009
DOI: 10.1063/1.3058694
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of on-state conductance with referenced electrochemical potential in ion gel gated polymer transistors

Abstract: We report direct measurement of the electrochemical potential at organic semiconductor/gate dielectric interfaces in printed polymer transistors employing a gel electrolyte as the gate insulator. An oxidized silver wire reference electrode was embedded into the gel electrolyte, and its potential relative to the grounded source contact was measured simultaneously with the transistor transfer characteristics. The referenced turn-on voltages of transistors based on three common polymer semiconductors [(poly-3-hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 16 publications
2
64
0
Order By: Relevance
“…The m FET calculated from gatedisplacement current gave more reasonable values (average m FET : B3.8 cm 2 V À 1 s À 1 ) than that calculated from equation (3). Although the induced carrier density is inversely proportional to m FET , the calculated m FET is much higher than those of general P3HT FET devices (Supplementary Table S1), because the large induced hole density fills the trap of the P3HT channel and smoothes the electrostatic potential variation that occurs in the channel due to trapped charges 29 . In addition, we found that the core-shell structure of P3HT:PEO-blend NWs and extended chain orientation of P3HT along the wire axis contributed to the high m FET of ion-gel-gated NW FETs (Supplementary Figs S6-S8, S15 and S16, and Supplementary Notes S7 and S8).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The m FET calculated from gatedisplacement current gave more reasonable values (average m FET : B3.8 cm 2 V À 1 s À 1 ) than that calculated from equation (3). Although the induced carrier density is inversely proportional to m FET , the calculated m FET is much higher than those of general P3HT FET devices (Supplementary Table S1), because the large induced hole density fills the trap of the P3HT channel and smoothes the electrostatic potential variation that occurs in the channel due to trapped charges 29 . In addition, we found that the core-shell structure of P3HT:PEO-blend NWs and extended chain orientation of P3HT along the wire axis contributed to the high m FET of ion-gel-gated NW FETs (Supplementary Figs S6-S8, S15 and S16, and Supplementary Notes S7 and S8).…”
Section: Resultsmentioning
confidence: 84%
“…Instead of thin-film FET model, m FET can be computed using gate-displacement current and induced carrier density (P i ), 28,29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These can be particularly prominent in electrolyte-gated OTFTs, due to sluggish ionic diffusion effects. 27 As represented in figure 1.a, the devices were fabricated in air on a glass substrate and bottom Au source and drain electrodes were defined by photolithography, forming a channel of width W = 2000 µm and length L = 10 µm, resulting in a reasonably large W/L ratio of 200. P3HT was then spin-coated at 2000 rpm from a 5 mg mL −1 solution in 1,2-dichlorobenzene in order to form thin-films of thickness ≈ 20 nm.…”
mentioning
confidence: 99%
“…A Ag/AgO electrode was fabricated by oxidizing a Ag wire with a diameter of 50 m by immersing in piranha solution (H 2 SO 4 /H 2 O 2 , 7 : 3) for 1 min. 29) The gate bias was repeatedly swept from À8 to 8 V with a rate of 3 mV/s at 300 K, and we simultaneously obtained a leakage current between the channel and the gate and sheet conductance of the channel by the four-terminal method. Figures 4(a) and 4(b) show the leakage current density and sheet conductance as a function of gate bias and potential of the reference electrode.…”
Section: Electrochemical Reaction Vs Electrostatic Carriermentioning
confidence: 99%